2015
DOI: 10.1080/87559129.2015.1041184
|View full text |Cite
|
Sign up to set email alerts
|

Red and green macroalgae for fish and animal feed and human functional food development

Abstract: Cereal and plant proteins are used frequently in the manufacture of animal, fish and human food products but are often deficient in essential amino acids. In contrast, macroalgal proteins contain all the essential amino acids and are a rich source of other bioactives including taurine, lipids, carotenoids and pigments. Furthermore, macroalgal proteins are a substrate for bioactive peptides generation. This paper discusses macroalgal bioactives and their potential use in fish, animal and human nutrition and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(85 citation statements)
references
References 111 publications
(128 reference statements)
4
81
0
Order By: Relevance
“…We acknowledge this contradicts the accepted paradigm that many seaweeds have a high concentration of protein with high proportions of essential amino acids (Fleurence, 1999;Fleurence et al, 2012;Garcia-Vaquero & Hayes, 2015). However, protein concentration calculated for seaweeds are often overestimated by the use of the animal-based 6.25 N-toprotein conversion factor, and more accurately should be determined using a N-to-protein factor of 5.0 (Angell, Mata, de Nys, & Paul, 2016).…”
Section: The Concentration Of Essential Amino Acids In Seaweedsmentioning
confidence: 75%
“…We acknowledge this contradicts the accepted paradigm that many seaweeds have a high concentration of protein with high proportions of essential amino acids (Fleurence, 1999;Fleurence et al, 2012;Garcia-Vaquero & Hayes, 2015). However, protein concentration calculated for seaweeds are often overestimated by the use of the animal-based 6.25 N-toprotein conversion factor, and more accurately should be determined using a N-to-protein factor of 5.0 (Angell, Mata, de Nys, & Paul, 2016).…”
Section: The Concentration Of Essential Amino Acids In Seaweedsmentioning
confidence: 75%
“…The protein content of brown macroalgae is generally low (usually below 150 g kg −1 of dry matter (DM)), whereas green macroalgae, and especially red macroalgae, have a higher protein content on a DM basis . Some red macroalgae, such as Porphyra spp., have protein levels comparable to soybean meal, for example …”
Section: Chemical Composition Of Macroalgaementioning
confidence: 99%
“…After drying and milling to a fine powder, macroalgae are traditionally used as seaweed meal in compound animal feed on a total biomass basis . Oven drying by fossil energy is energy intensive and costly, and other technologies may be applied . Recent research has shown that the addition of dilute hydrochloric acid reduces the stickiness of the biomass, rendering it suitable for dewatering by screw‐pressing, and the pH reduction may facilitate efficient preservation.…”
Section: Processing For Compound Feed Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Marine macroalgae are considered a rich source of micro- and macronutrients with antioxidant activities, i.e., minerals, carotenoids, phenolic compounds, proteins and polysaccharides [1]. …”
Section: Introductionmentioning
confidence: 99%